SOSIALISASI MEDIA PEMBELAJARAN PENDIDIKAN JASMANI BERBASIS KEARIFAN LOKAL, SENI TARI, INOVASI, NILAI BUDAYA DAN IDENTITAS NASIONAL - Irfandi; Zikrur Rahmat; Mansur; Is, Zulheri; Yoki Afriandy Rangkuti (Jurnal Pengabdian Keolahragaan dan Sains, 2025)
This activity aims to describe the process of socializing Physical Education learning media based on local wisdom, dance, innovation, cultural values, and national identity. The background of this activity departs from the need to develop learning media that are not only oriented towards improving the motor skills of students, but also integrating cultural and artistic values as a strengthener of national identity. The implementation of activities through socialization, observation, interviews, and documentation. Socialization activities were carried out in junior high schools involving PJOK teachers, students, and regional art communities. The results show that learning media prepared based on local wisdom and dance are able to increase student learning motivation, enrich movement experience, and instill cultural values that are in line with national identity. In addition, innovations in learning media make it easier for teachers to deliver material creatively and contextually. The research conclusion confirms that the socialization of learning media based on local wisdom, dance, and culture is not only effective in improving the quality of Physical Education learning, but also strategic in strengthening the character and national identity of the younger generation.